Overexpression of CsCaM3 Improves High Temperature Tolerance in Cucumber - Yu, Bingwei; Yan, Shuangshuang; Zhou, Huoyan; Dong, Riyue; Lei, Jianjun; Chen, Changming; Cao, Bihao (Frontiers in Plant Science, 2018)
High temperature (HT) stress affects the growth and production of cucumbers, but genetic resources with high heat tolerance are very scarce in this crop. Calmodulin (CaM) has been confirmed to be related to the regulation of HT stress resistance in plants. CsCaM3, a CaM gene, was isolated from cucumber inbred line ‘02-8.’ Its expression was characterized in the present study. CsCaM3 transcripts differed among the organs and tissues of cucumber plants and could be induced by HTs or abscisic acid, but not by salicylic acid. CsCaM3 transcripts exhibited subcellular localization to the cytoplasm and nuclei of cells. Overexpression of CsCaM3 in cucumber plants has the potential to improve their heat tolerance and protect against oxidative damage and photosynthesis system damage by regulating the expression of HT-responsive genes in plants, including chlorophyll catabolism-related genes under HT stress. Taken together, our results provide useful insights into stress tolerance in cucumber.